2016
DOI: 10.1111/rode.12256
|View full text |Cite
|
Sign up to set email alerts
|

Exchange Rate Flexibility and the Effect of Remittances on Economic Growth

Emmanuel K. K. Lartey

Abstract: This paper studies the question of whether exchange rate policy affects the impact of remittances on economic growth in recipient countries. The findings indicate that more flexible exchange rate regimes are associated with a greater increase in economic growth following an increase in remittances, but also that the impact of remittances on growth is positive under a fixed regime. The results further show that the effect of remittances under a fixed exchange rate regime is positive in less financially develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The findings determined that a bidirectional causality exists between exchange rate and remittances. Lartey (2017) studied the effect of remittances on GDP in 135 emerging and transition countries from 1970-2007. The results showed that a boost in economic growth and remittances is directly linked with a more flexible exchange rate.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The findings determined that a bidirectional causality exists between exchange rate and remittances. Lartey (2017) studied the effect of remittances on GDP in 135 emerging and transition countries from 1970-2007. The results showed that a boost in economic growth and remittances is directly linked with a more flexible exchange rate.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Migration of household members creates benefits and costs for those left behind, all of which could affect child human capital. Numerous studies find positive economic outcomes from such remittances, including increased demand for tradable goods and economic growth (Lartey, ; Lartey, ). At the microeconomic level, remittances can immediately reduce poverty and spur human capital accumulation.…”
Section: Past Findingsmentioning
confidence: 99%
“…In addition to the above discussed papers on the relationship between remittances and exchange rates, many papers have expanded the scope of research to investigate the relationship between remittances and many economic variables. Many studies investigated the economic significance of workers remittances on economic growth in recipient countries (Yang, 2005;Adams and Richard, 2008;Singer, 2010;Lartey, 2016). Adams and Richard (2008) -addresses this question by using new data on such variables as the skill composition of migrants, poverty, and interest and exchange rates to examine the determinants of remittances.…”
Section: Literature Reviewmentioning
confidence: 99%